Olfactory Inspection of Female Reproductive States in Chimpanzees - Jänig, Susann; Kücklich, Marlen; Kulik, Lars; Zetzsche, Madita; Weiß, Brigitte M.; Widdig, Anja (Frontiers in Ecology and Evolution, 2022)
In mammalian species, olfactory cues are important for within and between species communication. These cues can be part of multimodal signals indicating, for example, female fertility potentially perceived by male conspecifics. However, a large gap exists in our understanding of multimodal signaling in non-human catarrhines. Chimpanzees (Pan troglodytes) live in fission-fusion societies, mate promiscuously and express high levels of male-male competition. Females show a striking visual signal, an exaggerated sexual swelling, known to be a proxy of ovulation, while the maximum swelling is not matching the exact time of ovulation. The question remains if males use additional olfactory cues when being able to approach females closely. This would allow males to pinpoint the exact timing of ovulation and could be one reason why high-ranking males sire offspring more successfully than other males. Here, we present the first systematic test of such multimodal signaling by investigating male sniffing behavior directed to females in relation to their fertility in a group of 13 captive chimpanzees. Our results show that male sniffing behavior significantly increased with female swelling size, with female age as well as when fewer male competitors were present. Hence, odors might be part of a multimodal fertility cue, supporting the idea that males monitor both visual and olfactory cues to gain comprehensive information on female fertility.